0087 Simply the best: Using simulation technology and bite sized in-situ simulation to improve patient care. (2nd November 2015) - Jolly, Karen; Kilkie, Sharon; Harris, Patrick
Abstract : Clinical demands and a shortage of staff make it difficult to release ward staff for non-mandatory teaching. The Acutely Ill Recognition nurse and simulation team collaborated to deliver a one hour in-situ teaching for all grades of non-medical staff on two acute ward areas. The aims: Recognise and respond appropriately to a deteriorating patient. Accurately perform observations. Document observations on a track and trigger chart. Methodology: The simulation teaching was delivered to all ward staff, trained and untrained, over a four week period on an individual basis for up to one hour. Training consisted of a simulated scenario, clinical skills training and equipment update. The scenario required the member of staff to undertake 'normal' observations on the standardised patient and discuss technical aspects such as measuring blood pressure, disinfecting machinery and using the documentation. Simulation continued using a live actor with physiology generated by a SimPad. The ward staff were encouraged to use clinical reasoning to manage the patient and escalate care appropriately. Results: The results have been exciting; there has been a measurable sustained improvement in the completion of track and trigger observation charts and earlier appropriate escalation of deteriorating patients. There has also been a greater compliance with infection control procedures and staff have reported greater confidence following the teaching. Conclusion: These positive results have demonstrated that in situ simulation has a useful place in busy clinical areas. Although this method of teaching technical skills is time consuming for the education team it was extremely well received by the ward staff and this teaching is now being rolled out throughout the Trust. In-situ simulation allows ward staff to receive this critical training whilst remaining on the ward.